UMAT AWAM DALAM DINAMIKA HIDUP GEREJA - Antonius Denny Firmanto (Studia Philosophica et Theologica, 2011)
The article discusses the dignity and role of the Catholic laity. The author argues that the differentiation between the laity (laikos) and clerus (kleros) does not emerge in the Scriptures. The term used in the Scriptures is laos, which refers to the chosen people. The differentiation grew as a historical development and, to some extent, created an impression that the laity were the lower group in the Catholic Church. Second Vatican Council has promoted a fresh look at the laity. They are not simply the non-clerical members of the Church. Rather, they are equal members of the People of God with a unique vocation, stemming from one Baptism, to spread the Gospel in the temporal world.